IMPLEMENTASI TUGAS HAKIM PENGAWAS DAN PENGAMAT DALAM PENGAWASAN DAN PENGAMATAN TERHADAP NARAPIDANA (Kajian di Lembaga Pemasyarakatan Klas II A Purwokerto) - Dessy Perdani Yuris PS (Jurnal Dinamika Hukum, 2010)
The implementation of court judgments needs to be observed and perceived, thus the birth of Supervisor and Observer Judge Institution by Law No. 8 of 1981. The position of a Judge is not simply responsible for imposition of punishment, but also have to responsible for completion of punishment term by inmates in Correctional Institute by appropriate pattern and program of counseling. Besides in article 277 KUHAP till article 288 KUHAP it is charged another task as supervisor and observer of the court decision. The research results show that the implementation of the Supervisory Judge task and Observers in the execution of court decisions in Purwokerto Penitentiary is based on the Criminal Procedure Code Article 277 through Article 283 Criminal Procedure Code, the implementing regulations of the Supreme Court Circular No. RI. No. 7 of 1985. Supervisory Judge in the performance of duties and Observers in Purwokerto Penitentiary still met the constraints that are internal or external, internal resistance from law enforcement and the factors of factor means or facilities. Then the external barriers are the ruling factor.Keywords : Supervisor and Observer Judge, Purwokerto Penitentiary and prisoner